The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1016/j.rmed.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of decline in serum IgE levels in allergic bronchopulmonary aspergillosis

Abstract: A 35% decline in serum IgE levels at six weeks is not seen in all patients with ABPA, and the decline is slower in patients with baseline IgE levels <2500IU/mL. The quantum decline in serum IgE levels does not predict clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 22 publications
1
84
3
4
Order By: Relevance
“…Importantly, improvement in spirometric parameters at 6 weeks and time to first exacerbation were similar in the two groups, which further suggests that the IgE decline is of little significance. The clinical significance of a decline in serum IgE is not known and in one study the quantum decline in IgE was not a predictor of exacerbation in ABPA [19]. Due to a higher total steroid dose (almost 2.5 times higher), the frequency of adverse events (cushingoid habitus and weight gain) were significantly higher in the high-dose steroid arm.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Importantly, improvement in spirometric parameters at 6 weeks and time to first exacerbation were similar in the two groups, which further suggests that the IgE decline is of little significance. The clinical significance of a decline in serum IgE is not known and in one study the quantum decline in IgE was not a predictor of exacerbation in ABPA [19]. Due to a higher total steroid dose (almost 2.5 times higher), the frequency of adverse events (cushingoid habitus and weight gain) were significantly higher in the high-dose steroid arm.…”
Section: Discussionmentioning
confidence: 94%
“…Chest HRCT was used to classify ABPA as serologic ABPA, ABPA with bronchiectasis or ABPA with high-attenuation mucus [18]. The detailed methodology of each of the aforementioned investigations has been previously described [8, [19][20][21][22][23][24][25][26][27].…”
Section: Study Proceduresmentioning
confidence: 99%
“…Even after five decades of research this disorder is under diagnosed. In the developing countries, one-third of cases with ABPA are still misdiagnosed as pulmonary tuberculosis [5]. Though asthma is the most common contributing factor, ABPA is also seen in patients with cystic fibrosis and other underlying bronchiectatic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind the use of steroids in ABPA exacerbations is their ability to relieve airway obstruction, decrease sputum production and hasten resolution of pulmonary infiltrates due to their anti-inflammatory effects (inhibition of phospholipase A2 activity and arachidonic acid metabolism, decrease in inflammatory cell chemotaxis, cell adhesion and tissue infiltration, and diminished production of inflammatory cytokines) [14]. We have previously shown that the presence of severe bronchiectasis and high-attenuation mucus is associated with recurrent relapses [15][16][17]. Both our patients had severe bronchiectasis while one patient had high-attenuation mucus.…”
Section: Pulse Methylprednisolone In Allergic Bronchopulmonary Aspergmentioning
confidence: 99%